Tourism Employee Competence in The Artificial Intelligence Era - Indaryanto, Adrid; Purwono, Rudi; Lestari, Yetty Dwi; Sinaga, Eduard; Agusta, Yudi (International Journal of Basic and Applied Sciences, 2025)
The study aims to address the peculiarities of the professional development of hospitality workers in Bali in the context of the development of machine learning technologies. An empirical study was conducted, including a survey of industry employees. The study revealed the positive dynamics of Indonesia's gross domestic product, the share of the tourism segment in it, and the impact of the coronavirus pandemic. The key economic indicators of the Bali labour market, such as the unemployment rate, which has decreased from 6% to 2.7% since 2020, and the minimum wage, which has increased by IDR 400 thousand per month over 5 years, were discussed separately. Trends in the technological transition of the tourism industry to a new way of “Industry 4.0”, the introduction of “smart tourism” principles, and sustainable development goals were also studied. A 4-question survey was conducted among 120 employees of 12 hotels in 5 regions, which showed that most staff members are aware of the importance of using modern technologies and the need to improve self-efficacy. The practical significance of the study is determined by the evaluation of the effectiveness of a format in which humans and artificial intelligence do not compete but create a symbiotic pair.